Morfologia do sistema reprodutor masculino em espécies de heterópteros aquáticos - Igor Luiz Araújo Munhoz (2016)
The Hemiptera order is one of the largest in the Class Insecta, displaying great morphological variety of reproductive strategies and eating habits, occupying the most diverse terrestrial and aquatic environments. Within the Heteroptera suborder, the infraorder Nepomorpha contains the truly aquatic bugs that live in lotic and lentic environments. Different occupied ecological niches reflect in different adaptations and reproductive strategies. Variations in the morphology of reproductive systems can occur in the presence or absence of structures, number and position along the reproductive tract. When the external morphological characteristics are not enough to resolve taxonomic problems, additional information may be obtained by morphological and histological analysis of the internal organs. These interspecific variations in such structures have generated characters able of supporting phylogenetic analyzes. The inclusion of new characters added to the morphological characters commonly used, are intended to contribute to the system of various groups of insects that do not have a phylogeny fully accepted. Furthermore, these studies assist in the understanding of reproductive biology such as different mating strategies. In this thesis, we describe the morphology and histology of the male reproductive system in species of Belostomatidae and Naucoridae families of the order Hemiptera. For this, we used techniques of light microscopy. The results demonstrate similarities and differences with other studies in the literature and point characters such as: (1) general anatomy; (2) number of follicles per testis; (3) the number of cysts by sperm, and (3) histology of the reproductive system; potential for future inferences in systematic, emphasizing the need for description of the anatomy and histology of the male reproductive system in a larger number of species